2015
DOI: 10.4236/ojss.2015.51003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Land Use Change on Land Degradation Reflected by Soil Properties along Mara River, Kenya and Tanzania

Abstract: Human-induced changes to natural landscapes have been identified as some of the greatest threats to freshwater resources. The change from natural forest cover to agricultural and pastoral activities is rampant especially in the upper Mara River catchment (water tower), as well as along the course of the Mara River. The objective of this study was to determine the effect of land use change on the physico-chemical properties of soil (bulk density, carbon, nitrogen, phosphorus and pH) along the course of the Mara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…This growth rate translates to an increased pressure and demand for land resources especially in the watershed regions such as Mau Forest Complex. As a result, there is continuing watershed degradation reflected through diminishing forest cover, reduced water quality, soil productivity, loss of riparian vegetation and wetland areas leading to a decline in the ecological stability of these systems (Matano et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This growth rate translates to an increased pressure and demand for land resources especially in the watershed regions such as Mau Forest Complex. As a result, there is continuing watershed degradation reflected through diminishing forest cover, reduced water quality, soil productivity, loss of riparian vegetation and wetland areas leading to a decline in the ecological stability of these systems (Matano et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this rapid change, and in contrast to the vast literature on agricultural soils, only few studies have examined the effects of the long-term conversion from grassland or cropland on soil properties in mountain forest ecosystems (Skousen et al 1998). Historical review on landuse in the mountain zones in Bulgaria showed that past forests have been threatened by excessive and improper use by the local population, which has led to replacement of typical tree species by others (Masarov 1940, Alexandrov 1994. In Bulgaria, afforestation is of high importance for mountain ecosystems, and substantial land conversion took place during the last decades to contrast erosion, to increase the treeline zone and to use low-productive areas.…”
Section: Introductionmentioning
confidence: 99%
“…Soil bulk density is the major discriminating factor in soil properties in relation to land use and management (Tisdall & Oades 1982, Zenga et al 2014, Matano et al 2015. Soil bulk density integrates effects of management and OM decline; these factors in conjunction result in smaller pore volumes and thus higher bulk densities.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Grazing by wild ungulates naturally differs from livestock grazing (Jackson and Bartolome, 2007). Depending on the number of stocking rate, ungulate type (wild or domestic) and grazing periods, grazing practices affect soil properties APPLIED Matano et al, 2015). High grazing intensity leads to decreasing nutrient availability resulting in soil fertility reduction (Morgan, 1995;Hiernaux et al, 1999;Connolly et al, 2016).…”
Section: Introductionmentioning
confidence: 99%